The ghost next door - Stine, R. L. (United Kingdom : Scholastic, 2015)
After a new boy moves in next door, Hannah wonders if she's being haunted by a ghost next door.
Primary
Keywords: Ghosts -- Fiction; Horror stories; Ghost stories; Neighbors -- Fiction